2010
DOI: 10.1590/s1413-86702010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of leishmaniasis at a reference service in the state of Alagoas, Brazil, from january 2000 to september 2008

Abstract: Leishmaniasis is a parasitic disease found in the continents of Europe, Asia, Africa and the Americas. In Brazil, the disease is an important public health problem, occurring in most states, but mainly in the Northeast region of the country, with the state of Alagoas having a signifi cant number of confi rmed cases. The present study establishes and discusses the epidemiological profi le of cases of leishmaniases treated at the Reference Center of Alagoas, Hospital Escola Hélvio de Farias Auto, between January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
2
6
1
10
Order By: Relevance
“…In the present study, 95.0% of patients with the cutaneous form and 85.7% of those with the mucosal form were considered to be cured, which were higher than those (59.1%) described in Northern Paraná State (17) , in Alagoas State (44.5%) (19) , and in Rio de Janeiro State (74%) (32) . Similar results were reported by Name et al (28) who found a clinical cure rate of 81.6% in patients with the cutaneous form and 69.6% in patients with the mucocutaneous form in Brasília.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In the present study, 95.0% of patients with the cutaneous form and 85.7% of those with the mucosal form were considered to be cured, which were higher than those (59.1%) described in Northern Paraná State (17) , in Alagoas State (44.5%) (19) , and in Rio de Janeiro State (74%) (32) . Similar results were reported by Name et al (28) who found a clinical cure rate of 81.6% in patients with the cutaneous form and 69.6% in patients with the mucocutaneous form in Brasília.…”
Section: Discussioncontrasting
confidence: 63%
“…In the same area, Silveira et al (7) described MST positivity in 95.1%, whereas Curti et al (14) described MST positivity in 92.3% with cutaneous form ATL. Pontello et al (17) exhibited 84.4% positivity, Nunes et al (19) exhibited 56.1% positivity, and Murback et al (27) exhibited 91.4% positivity for MST among the ATL cases.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nunes et al 8 ,. also in the state of Alagoas , described an epidemiological profile of patients with leishmaniasis who were treated in a referral hospital.…”
Section: Introductionmentioning
confidence: 98%
“…Compreendem um espectro de doenças distribuídas mundialmente em regiões tropicais e subtropicais, com a capacidade de se adaptar a diferentes ecossistemas e infectar diferentes espécies de mamíferos (WORLD HEALTH ORGANIZATION, 2012;NUNES et al, 2010).…”
Section: Introductionunclassified